Association of vitamin D level with systemic lupus erythematosus: A case - control study - Mrinal Saha; Aparana Deb; Imtiaz Sultan; Md Abdur Razzaque; Sakit Mahmud; Abu Kamran Rahul; Khaled Hassan; Sujat Paul (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune connective tissue disease. SLE patients are more prone to vitamin D deficiency because of their light sensitivity, renal involvement, and prolonged steroid use. This current study aimed to determine the relationship between vitamin D deficiency and SLE.